The Duffy antigen receptor for chemokines, ACKR1, – 'Jeanne DARC' of benign neutropenia. (27th December 2018) - Rappoport, Naama; Simon, Amos J.; Amariglio, Ninette; Rechavi, Gideon
Summary: Benign neutropenia, observed in different ethnic groups, is the most common form of neutropenia worldwide. A specific single nucleotide polymorphism, rs2814778, located at the promoter of the ACKR1 (previously termed DARC ) gene, which disrupts a binding site for the GATA1 erythroid transcription factor, resulting in a ACKR1 ‐null phenotype, was found to serve as a predictor of low white blood cell and neutrophil counts in African‐Americans and Yemenite Jews. Individuals with benign neutropenia due to the ACKR1 ‐null allele have been found to have an increased susceptibility to human immunodeficiency virus infection and, on the other hand, a protective effect against malaria. The associated protective effect may explain the spread of the ACKR1 ‐null allele by natural selection. The reviewed relationships between ACKR1 polymorphism and various pathological states may have important clinical implications to individuals with and without benign neutropenia. Potential mechanisms for ACKR1 (previously termed DARC) modulation during neutrophil recruitment to inflammation, and chemokine bioavailability in the circulation and in local tissue are reviewed and discussed.